Cooperative phenomenon of vapochromism and proton conduction of luminescent Pt(ii) complexes for the visualisation of proton conductivity. (23rd October 2020) - Kobayashi, Atsushi; Imada, Shin-ichiro; Wang, Dongjin; Nagao, Yuki; Yoshida, Masaki; Kato, Masako
Abstract : The cooperative phenomenon between proton conduction and vapochromism of luminescent Pt(ii ) complexes, [PtCl(tpypy)]Cl and [PtCl(tpypyH)]Cl2, is reported. Abstract : The luminescent and proton conductive Pt(ii ) complex [PtCl(tpy- o -py)]Cl and its HCl adduct [PtCl(tpy- o -pyH)]Cl2 ( o -Pt and o -Pt·HCl, respectively; tpy- o -py = 2, 2′:6′, 2′′-terpyridine-6′, 2′′′-pyridine) were synthesised and their crystal structures, vapochromic behaviour, and proton conduction, were investigated and compared to those of the para isomers [PtCl(tpy- p -py)]Cl and [PtCl(tpy- p -pyH)]Cl2 ( p -Pt and p -Pt·HCl, respectively; tpy- p -py = 2, 2′:6′, 2′′-terpyridine-4′, 4′′′-pyridine). X-ray structure analysis revealed that the intermolecular metallophilic (Pt⋯Pt) interaction was negligible in o -Pt but effective in o -Pt·HCl . Reversible transformation between o -Pt and o -Pt·HCl coupled with significant colour and luminescence changes was achieved by four different external stimuli, namely: exposure of o -Pt to humid HCl gas to form o -Pt·HCl, heating, exposure to MeOH vapour, and finally drying in air to regenerate the original o -Pt . The intraligand π–π* orange emission observed for o -Pt exhibited negligible dependence on the relative humidity (RH). Conversely, o -Pt·HCl exhibited red metal–metal-to-ligand charge-transfer (MMLCT) phosphorescence at 725 nm, originating from effective intermolecular Pt–Pt interactions, and interesting vapochromic behaviour that was dependent on the RH. Notably, o -Pt·HCl presented higher conductivity than the p -Pt·HCl isomer at RH < 80%. This trend was reversed at RH values > 80%, probably owing to the second water-adsorption-induced transformation of p -Pt·HCl . The cooperative phenomenon between the proton conduction and vapochromic behaviour observed for both o -Pt·HCl and p -Pt·HCl should allow the visualisation of the proton-conducting pathway, without the need for a bulk electrode, via the absorption and emission colours at both macroscopic and microscopic levels.